Between conflicts and partnerships: Managing the UNESCO World heritage label in peripheral and metropolitan urban regions in Europe - Carola Silvia Neugebauer (European Regional Science Association (ERSA), 2014)
The UNESCO world heritage label (WHL) is a contentious topic in local to global public, and it gains in importance for the urban and regional development in Europe for some reasons. So on the one hand, the nominations of European sites as UNESCO world heritage are increasing steadily, and on the other hand the polarization of space is still continuing. Thus, the disparities between peripheral and metropolitan regions and their towns are growing. The need to steer sustainably the economic, demographic and cultural concentration processes in metropolises confronts the challenge in peripheral regions to stabilize and initiate developments. In consequence of these trends the UNESCO world heritage label constitutes a relevant urban and regional topic that refers to conflicting connotations like 'development barrier' and 'source of conflict' on the one hand, and 'chance for development' on the other. To date, however, the potential of the WHL for sustainable urban and regional development is barely investigated. Neither the local socio-cultural, economic and institutional effects of the world heritage status, nor the mechanisms and conditions of its local effectiveness have been investigated in a critical and systematic way. Moreover, there is little research on the local management approaches, how to enhance (save and use) the UNESCO label for sustainable urban development which should be based on the principles of integration, participation and justice. Against this background, a recent research project evaluated the UNESCO world heritage label as potential for urban sustainable development. Mindful of the intertwined local to global contextual dimensions and actor networks it questioned the hypotheses that the spatial (peripheral and metropolitan) context of an urban region and the local actors' concepts and activities towards the WHL do influence the status' impacts on urban development. A special emphasis was given to the analysis of local partnerships, planning instruments and communication processes, tackling the UNESCO label as potential for urban development. Based on a realist evaluation approach that links economic and social theory with comparative case study research in the three European world heritage cities of St. Petersburg (Russia), Stralsund and Wismar (Germany), the project finally proves the WHL as a topic of cross-sectoral importance for urban regions, affecting collaterally political and administrative as well as economic and socio-cultural local processes and structures in a positive or negative way. The WHL constitutes a potential for sustainable urban development indeed, but in dependence on the spatial context of an urban region as well as on the local actors' approaches, how to enhance the WHL. Mindful of these insights, the project argues for spatially differentiated and actor sensitive local management approaches in order to preserve the urban world heritage and to use the WHL for socio-cultural and economic sustainable development.
Keywords: 330; urban sustainability; UNESCO world heritage label; urban governance; evaluation research